Influence of Cytotoxic Drugs on Platelet Functions and Coagulation in vitro. - Klener, P; Kubisz, P; Suranová, J (Thrombosis and Haemostasis, 1977)
Influence of melphalan on some platelet functions, plasmatic coagulation and fibrinolysis “in vitro” was investigated, using different concentrations of the drug (25, 50 and 250 μg/ml). The lowest concentration slightly inhibited adrenaline and/or collagen-induced platelet aggregation. Following the highest concentration of the drug, strong inhibition of aggregation was recorded, regardless of the inducer used. Melphalan was also shown to inhibit release of aggregating activity and release of platelet factor 4, as well as availibility of platelet factor 3 and platelet acid phosphatase. The intensity of inhibition depended on both, melphalan concentration and the time of preincubation. In contrast to this, adhesion of platelets to glass slide was not found to be influenced by melphalan. Similarly, melphalan did not induce (in any concentration) loss of LDH from platelet cytoplasma, while triton X-100 or freezing and thawing of platelets caused significant increase of LDH activity. From coagulation tests studied, only thrombin time and reptilase time was found to be moderately prolonged in the presence of melphalan.Authors assumed that melphalan acts as a specific inhibitor of release reaction and can induce an acquired thrombocytopathy. The platelet membrane is not damaged by the drug, as was confirmed by the investigation of LDH activity. Influence on coagulation indicates some antithrombin effect of the drug. Although presented results were obtained in vitro, analogous changes in vivo could be suspected. Thus, impairement of platelet functions might play a part in haemorrhagic complications accompanying, in some cases, melphalan therapy.